A DETERMINATION OF EMPLOYEE PERFORMANCE BASED ON LEADERSHIP STYLE, DISCIPLINE, AND WORK CULTURE ON MOTIVATION AS AN INTERVENING VARIABLE - rosita, eni (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose:knowing and analyzing the influence of leadership style on motivation, the influence of work discipline on motivation, the influence of work culture on motivation, the influence of leadership style, discipline, and work culture on motivation, knowing the influence of leadership style on performance, knowing the influence of discipline on performance, knowing the influence of work culture on performance, knowing the influence of leadership style, work culture, and work discipline on performance, and knowing the influence of work motivation on performance. Design/methodology/approach:The method used in this study is quantitative, with the analysis tool used SmartPLS4. Respondents in this study were 72 people. The sampling technique used was probability sampling. Data collection was done through field work research and library research. Findings:The results of the study showedleadership style has a significant effect on work motivation, work discipline has a significant effect on employee work motivation, work culture has a significant effect on employee work motivation, leadership style, work discipline, and work culture have a significant effect on employee work motivation, leadership style has a significant effect on employee performance, work discipline has a significant effect on employee performance, work culture has a significant effect on employee performance,leadership style, work discipline, and work culturesignificantly influence employee performance, and work motivation has a significant effect on employee performance. Suggestions that can be made are several training activities and family gathering activities to strengthen the sense of family and respect so that they motivate each other in achieving the vision, mission, and goals of the organization. Research limitations/implications:Time Limitation Practical implications:Practical implications and theoretical implications Originality/value:The originality of this research is based on several previous studies that have relatively similar characteristics in terms of study themes, although they differ in terms of subject criteria, number and position of research variables or analysis methods used. Key words:Leadership Style, Discipline, Work Culture, Motivation, and Performance